Efficacy and safety of abrocitinib in adults and adolescents with moderate-to-severe atopic dermatitis (JADE MONO-1): a multicentre, double-blind, randomised, placebo-controlled, phase 3 trial. Issue 10246 (25th July 2020) - Simpson, Eric L; Sinclair, Rodney; Forman, Seth; Wollenberg, Andreas; Aschoff, Roland; Cork, Michael; Bieber, Thomas; Thyssen, Jacob P; Yosipovitch, Gil; Flohr, Carsten; Magnolo, Nina; Maari, Catherine; et al.
Summary: Background: Abrocitinib, an oral selective Janus kinase 1 inhibitor, was effective and well tolerated in adults with moderate-to-severe atopic dermatitis in a phase 2b trial. We aimed to assess the efficacy and safety of abrocitinib monotherapy in adolescents and adults with moderate-to-severe atopic dermatitis. Methods: In this multicentre, double-blind, randomised phase 3 trial (JADE MONO-1), patients (aged ≥12 years) with moderate-to-severe atopic dermatitis (Investigator Global Assessment score ≥3, Eczema Area and Severity Index [EASI] score ≥16, percentage of body surface area affected ≥10%, and Peak Pruritus Numerical Rating Scale score ≥4) with a bodyweight of 40 kg or more, were enrolled at 69 sites in Australia, Canada, Europe, and the USA. Patients were randomly assigned (2:2:1) to oral abrocitinib 100 mg, abrocitinib 200 mg, or placebo once daily for 12 weeks. Randomisation was done using an interactive response technology system, stratified by baseline disease severity and age. Patients, investigators, and the funder of the study were masked to study treatment. The coprimary endpoints were the proportion of patients who had achieved an Investigator Global Assessment response (score of 0 [clear] or 1 [almost clear] with a ≥2-grade improvement from baseline), and the proportion of patients who achieved at least a 75% improvement in EASI score from baseline (EASI-75) score, both assessed at week 12. Efficacy was assessed in the full analysis set, which included all randomised patients who received at least one dose of study medication. Safety was assessed in all randomised patients. This study is registered with ClinicalTrials.gov, NCT03349060 . Findings: Between Dec 7, 2017, and March 26, 2019, 387 patients were enrolled: 156 were assigned to abrocitinib 100 mg, 154 to abrocitinib 200 mg, and 77 to placebo. All enrolled patients received at least one dose of study treatment and thus were evaluable for 12-week efficacy. Of the patients with available data for the coprimary endpoints at week 12, the proportion of patients who had achieved an Investigator Global Assessment response was significantly higher in the abrocitinib 100 mg group than in the placebo group (37 [24%] of 156 patients vs six [8%] of 76 patients; p=0·0037) and in the abrocitinib 200 mg group compared with the placebo group (67 [44%] of 153 patients vs six [8%] of 76 patients; p<0·0001). Of the patients with available data for the coprimary endpoints at week 12, compared with the placebo group, the proportion of patients who had achieved an EASI-75 response was significantly higher in the abrocitinib 100 mg group (62 [40%] of 156 patients vs nine [12%] of 76 patients; p<0·0001) and abrocitinib 200 mg group (96 [63%] of 153 patients vs nine [12%] of 76 patients; p<0·0001). Adverse events were reported in 108 (69%) of 156 patients in the abrocitinib 100 mg group, 120 (78%) of 154 patients in the abrocitinib 200 mg group, and 44 (57%) of 77 patients in the placebo group. Serious adverse events were reported in five (3%) of 156 patients in the abrocitinib 100 mg group, five (3%) of 154 patients in the abrocitinib 200 mg group, and three (4%) of 77 patients in the placebo group. No treatment-related deaths were reported. Interpretation: Monotherapy with oral abrocitinib once daily was effective and well tolerated in adolescents and adults with moderate-to-severe atopic dermatitis. Funding: Pfizer.